Development of E-Learning Management Model for Teaching System at The Police Academy - Fakhruddin, Rusdarti, Kardoyo, Elisa Ika Yuniawati (Turkish journal of computer and mathematics education, 2021)
This study aims to describe the development of  e-learning management model for the teaching system at the Police Academy through management of educational information systems. The method used is research and development (R&D). The development of e-learning management model for the teaching system as a research focus based on the Technology Accepted Model (TAM) theory and the education management information system input process output. The resulting model product is in accordance with the needs of police academy cadets in the use of e-learning. The product developed is an e-learning management system through an input output process. The results of a questionnaire to 100 Akpol cadets show that the e-learning management model of the teaching system is effective in providing convenience and information related to teaching at the Police Academy.